2010
DOI: 10.1016/j.cellsig.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Transdominant regulation of integrin function: Mechanisms of crosstalk

Abstract: Transdominant inhibition of integrins or integrin-integrin crosstalk is an important regulator of integrin ligand binding and subsequent signaling events that control a variety of cell functions in many tissues. Here we discuss examples of integrin crosstalk and detail our current understanding of the molecular mechanisms that are involved in this receptor phenomenon. The cytoskeleton associated protein talin is a key regulator of integrin crosstalk. We describe how the interaction of talin and the cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…Modulation of ␤ 2 integrins is currently used in the treatment of autoimmune diseases (32). Our results show that this may affect not only LFA-1 but also VLA-4 and, possibly, other integrins, which must be taken into consideration in the interpretation of the clinical outcome.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Modulation of ␤ 2 integrins is currently used in the treatment of autoimmune diseases (32). Our results show that this may affect not only LFA-1 but also VLA-4 and, possibly, other integrins, which must be taken into consideration in the interpretation of the clinical outcome.…”
Section: Discussionmentioning
confidence: 93%
“…After that, the phenomenon has been reported in other cell types and between different integrin subclasses. Although, in many cases, the outside-in activation through ligand binding of one integrin decreases the activity of another integrin, there are reports that show an opposite effect (32,33). It has been shown that the activation of LFA-1 can affect VLA-4 activity in T cells (34), but the mechanism has not been known.…”
Section: Discussionmentioning
confidence: 96%
“…Such crosstalk is known to occur between integrin β3 and another fibronectin-binding family member, integrin β1 (Gonzalez et al, 2010). To address the potential of crosstalk between these two integrins, we tested the possibility that downregulation of integrin β3 is accompanied by an increase in the activation of integrin β1.…”
Section: Downregulation Of Integrin β3 Is Not Accompanied By Increasementioning
confidence: 99%
“…S2E), supporting a defect in MuPyV signaling. Although these data suggest a role for α4-integrin in MuPyV signal activation, it is possible that a reduction in α4-integrin levels nonspecifically alters signaling pathways, and the defect we observed was not a consequence of MuPyV binding (32). Therefore, we next tested whether pseudoviruses that are unable to bind integrins or gangliosides affect signal activation, without modifying cell surface receptor expression or cellular signaling pathways.…”
Section: Resultsmentioning
confidence: 62%